Back Cover:Synthesis of Lithium Iron Phosphate/Carbon Microspheres by Using Polyacrylic Acid Coated Iron Phosphate Nanoparticles Derived from Iron(III) Acrylate (ChemSusChem 6/2015). Issue 6 (10th March 2015) - Xu, Dongwei; He, Yan‐Bing; Chu, Xiaodong; Ding, Zhaojun; Li, Baohua; He, Jianfu; Du, Hongda; Qin, Xianying; Kang, Feiyu
<x xml:space="preserve">Abstract</x> The Back Cover picture shows that iron(III) acrylate can be used as precursor for both iron and carbon source of lithium iron phosphate/carbon microspheres with high rate and cycling performance. FePO4 nanoparticles are first produced by a co‐precipitation reaction. The acrylic acid ions produced as a by‐product are in situ polymerized into a uniform polyacrylic acid layer coated on the surface of FePO4 nanoparticles. The utilization of by‐product is good from a sustainability point of view. More details can be found in the Full Paper by Xu et al. on page 1009 (DOI: 10.1002/cssc.201403060).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>